PERSEPSI GURU OLAHRAGA SEKOLAH DASAR DI KECAMATAN KAMPAR KIRI TERHADAP PEMBELAJARAN MEMALUI MEDIA DARING - Rafi Nurdiansyah; Zainur Zainur; Hirja Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The current problem that arises in elementary schools in Kampar Kiri District according to research observations is that teachers still vary in the physical education learning process in elementary schools, so that many problems arise during the physical education learning process. These include inadequate facilities and infrastructure, lack of student motivation in the learning process, lesson plans that have not changed from year to year, and learning evaluations that have not been optimally carried out by physical education teachers and the educational background of physical education teachers on average have an undergraduate degree. The aim of the researcher is to see how the physical education teacher's perception of physical education learning at Elementary Schools in Kampar Kiri District. The population of this study included all 27 elementary school physical education teachers in Kampar Kiri District. In this study, sampling was carried out using the Total Sampling technique where the entire population was sampled. The instrument of this research is in the form of a questionnaire filled out by the research object.From the results of the research that has been carried out, the following conclusions can be drawn: Overall the results of the percentage score of the average level of perception of physical education teachers on physical education learning planning is 81.64% in the very good category. Overall the results of the percentage score of the average level of perception of physical education teachers on the physical education learning process is 78.51% in the good category. Overall the results of the percentage score of the average level of perception of physical education teachers on the implementation of the physical education learning evaluation is 68.06% in the good category.Key Words: Perception, ExecutionPhysical Education Learning